Distribusi spasial nitrat air tanah di Kecamatan Nanggulan, Kulon Progo, Yogyakarta - Falah, Fajrul; Sejati, Sadewa Purba (Universitas Negeri Yogyakarta, 2023)
Residential areas in Nanggulan sub-district are mainly adjacent to irrigated rice fields. Groundwater in settlements close to irrigated rice fields has the potential to be contaminated with nitrates. Studies on the spatial distribution of groundwater nitrate around irrigated rice fields have never been conducted in Nanggulan District, Kulon Progo Regency. The study was conducted to determine the spatial distribution of nitrates in groundwater in Nanggulan District, Kulon Progo Regency. Nitrate data were collected through groundwater sample testing. The location of groundwater samples is determined using a systematic random sampling. The data was analyzed by spatial interpolation method through Arc GIS 10.6 software. The results showed variations in the spatial distribution of nitrates in the study area. Most of the study area had nitrate levels of 5-10 mg / L distributed in the south. Nitrates exceeding ten mg/L were distributed in the northern part of the study area. Based on research that has been conducted, it is known that 41% of groundwater in the study area is contaminated with nitrates, while 59% of groundwater is not contaminated with nitrates. Spatially, nitrate-contaminated groundwater is found in parts of Tanjungharo Village, some Wijimulyo Village, some Donomulyo Village, some Jatisarono Village, and some Kembang Villages. Groundwater not contaminated with nitrates is found in Banyuroto Village and most areas of Donomulyo Village. Factors that cause nitrate-contaminated groundwater are the location of excavated wells close to intensively fertilized irrigated rice fields, groundwater contained in geological formations of young Merapi volcano deposits, and groundwater depth of less than 5 meters.